A survey on agriculture and greenhouse monitoring using IOT and WSN - Lavanya, M; Srinivasan, Sujatha (International Journal of Engineering and Technology, 2018)
Internet of things (IoT) is connecting physical objects around us; those physical objects can be monitored with the help of sensors. A sensor is a device, which is used to sense physical property of an element, any events or any changes present in the environment and send the in-formation to other electronic device, frequently a computer. Many research are made on those sensor enabled IoT system to provide intelli-gent and smart services, towards smart greenhouse and smart agriculture .This paper will explore various existing IoT based agriculture and greenhouse system according to their deployment with an intension of identifying how it can be improved in future using IoT, WSN and a very recent scenario of using cloud computing.Â Â Â